MODELING CONTROL PROCESSES OF UNSTEADY SEPARATED FLOW IN THE NEAR WAKE - V. T. Kalugin; A. S. Epikhin; E. A. Tsykunova (Научный вестник МГТУ ГА)
The paper shows possibility of implementing the open source CFD software package OpenFOAM for calculation of unsteady vortex flows in researching of flow past cylinder with plate. Flow structure and aerodynamic characteristics have been obtained, and evaluation of the perturbations caused by the vortex shedding from the surface of cylinder has been conducted. Method of flow control in the region of the near wake has been proposed.